Whole Atmosphere Simulation of Anthropogenic Climate Change - Stanley C. Solomon; Han‐Li Liu; Daniel R. Marsh; Joseph M. McInerney; Liying Qian; Francis M. Vitt (Geophysical Research Letters)
Abstract We simulated anthropogenic global change through the entire atmosphere, including the thermosphere and ionosphere, using the Whole Atmosphere Community Climate Model‐eXtended. The basic result was that even as the lower atmosphere gradually warms, the upper atmosphere rapidly cools. The simulations employed constant low solar activity conditions, to remove the effects of variable solar and geomagnetic activity. Global mean annual mean temperature increased at a rate of +0.2 K/decade at the surface and +0.4 K/decade in the upper troposphere but decreased by about −1 K/decade in the stratosphere‐mesosphere and −2.8 K/decade in the thermosphere. Near the mesopause, temperature decreases were small compared to the interannual variation, so trends in that region are uncertain. Results were similar to previous modeling confined to specific atmospheric levels and compared favorably with available measurements. These simulations demonstrate the ability of a single comprehensive numerical model to characterize global change throughout the atmosphere.